Catalytic oxidative desulfurization of Malaysia diesel utilizing palm kernel shell activated carbon supported cerium/iron oxide - Nurul Syafiqah Mohd Zain, 1994- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains (Kimia) - Universiti Teknologi Malaysia, 2017